Mechanical dispersion is associated with clinical and subclinical coronary artery disease in patients on chronic renal replacement therapy with normal left ventricular ejection fraction. (8th February 2021) - Stefanovic, M; Stankovic, I; Jemcov, T; Janicijevic, A; Zec, N; Kusic Milicevic, J; Markovic, M; Vidakovic, R; Neskovic, AN
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Since coronary artery disease (CAD) is the leading cause of mortality in patients with end-stage renal failure, early detection of CAD in these patients presenting with still normal left ventricular (LV) systolic function is of clinical importance. Aim: To investigate the correlation between electrical and mechanical dispersion and CAD in dialysis patients with normal LV systolic function. Material and methods: This prospective study included 78 dialysis patients who underwent a 12-channel electrocardiogram and echocardiographic examination to determine electrical and mechanical myocardial dispersion. A coronary calcium score using cardiac computed tomography was also assessed in a group of 20 patients without known CAD. Electrical dispersion was defined as the difference between the longest and shortest corrected QT interval (QTc). Mechanical dispersion (MD) was defined as either standard deviation of mechanical contraction duration of all LV segments (MD_SD) or the difference between the longest and shortest duration of mechanical contraction (MD_delta). The duration of mechanical contraction was determined by myocardial strain analysis. Results: Previously known CAD was present in 11 (14%) patients, while pathologic Q wave was absent in all patients. No significant correlation was observed between QTc dispersion and both MD parameters (p > 0.05 for both). Both MD parameters (p = 0.007 for MD_SD; p = 0.026 for MD_delta), but not electrical dispersion (p = 0.584), showed a discriminative power for detecting previously known CAD (Figure). In patients without known CAD, neither QTc dispersion nor MD_SD showed a correlation with coronary calcium score (p > 0.05 for both). MD_delta showed a strong correlation with both total and coronary calcium score in the territory of the left anterior descending coronary artery (r = 0.62; p = 0.004) in patients without previously known CAD. Conclusion: Mechanical dispersion is associated with known CAD in dialysis patients with normal LV systolic function. The range of mechanical myocardial contraction duration (MD_delta) correlates with subclinical coronary atherosclerosis. Figure. Discriminative power of mechanical and electrical dispersion for the detection of coronary artery disease